UTM wins business competition: LEARNING EXPERIENCE: 75 varsity students take part in second edition of UUM event - Kumar, Punitha (New Straits Times, 2013)
IT took Chim Wei Wen and her team members only three days to prepare their winning business proposal. Despite the time constraints, the "chief executive officer" (CEO) of EZ Sdn Bhd said their proposal on EZ refillable markers was a success because of great teamwork.